PHYSICOCHEMICAL AND TECHNOLOGICAL CHARACTERIZATION OF SORGHUM BICOLOR (L.) MOENCH (SORGHUM) FLOURS - Jorge Rodríguez, María Elisa; Saucedo Hernández, Yanelis; Alba de Armas, Miguel Ángel; Estupiñán Pérez, Laura; Prendes Rodríguez, Ana Lurdes; Saucedo Castillo, Orlando Miguel (Centro Azúcar Journal, 2024)
Introduction: Sorghum bicolor (L.) Moench is the fifth most important cereal in the world. Due to its chemical composition, it is recommended for human consumption, especially for people with celiac disease, as it does not contain gluten. Sorghum flours from the Agricultural Research Center of the Universidad Central “Marta Abreu” of Las Villas do not have physicochemical and technological studies for their use in human nutrition. Objective: To check that flours of sorghum cultivars (Sorghum bicolor (L.) Moench meet the physicochemical and technological requirements demanded for nutritional products. Materials and Methods: Densities (apparent, apparent by settling and real), porosity, particle size distribution analysis, fluidity and hygroscopicity were determined. The extracts were qualitatively evaluated by Thin Layer Chromatography and phytochemical screening. Results and Discussion: The densities of all flours coincided with what was described in the standard. The flours of cultivars 21 and 74 presented a more uniform distribution of particle size and a lower percentage of fine dust. Cultivars 19 and 20 were slightly hygroscopic. The following were identified in the aqueous and ethanolic extracts: coumarins, alkaloids, phenols, tannins and flavonoids. Chromatographic analysis revealed coumarins and flavonoids. Conclusions: Cultivar 21 was integrally the one with the best technological properties. Coumarins and flavonoids were identified in all cultivars using qualitative techniques. The results contribute to the certification of flours, according to international requirements and the Codex standard, for use in human nutrition.